Identification and Control of Latent Bacteria in in vitro Cultures of Sweetpotato [Ipomoea batatas (L.) Lam] - Izarra, Myriam Lorena; Panta, Ana Luz; Maza, Carmen Rosa; Zea, Brenda Carina; Cruzado, Juan; Gutarra, Liliam Rosario; Rivera, Cristina R.; Ellis, David; Kreuze, Jan Frederik (Frontiers in Plant Science, 2020)
Bacterial microorganisms which are latent in in vitro cultures can limit the efficiency of in vitro methods for the conservation of genetic resources. In this study we screened 2373 accessions from the in vitro sweetpotato germplasm collection of the International Potato Center in Lima, Peru for bacteria associated with plantlets in tissue culture through a combination of morphological methods and partial 16S rDNA sequencing. Bacteria were detected in 240 accessions (10% of the accessions screened) and we were able to isolate 184 different bacterial isolates from 177 different accessions. These corresponded to at least nineteen Operational Taxonomic Units (OTUs) of bacteria, belonging to the genera Sphingomonas, Bacillus, Paenibacillus, Methylobacterium, Brevibacterium, Acinetobacter, Microbacterium, Streptomyces, Staphylococcus and Janibacter. Specific primers were developed for PCR based diagnostic tests that were able to rapidly detect these bacteria directly from tissue culture plants, without the need of microbial sub-culturing. Based on PCR screening the largest bacterial OTUs corresponded to a Paenibacillus sp. closely related to P. taichungensis (41.67%), and Bacillus sp. closely related to B. cereus (22.22%), and B. pumilus (16.67%). Since in vitro plant genetic resources must be microbe-free for international distribution and use, any microbial presence is considered a contamination and therefore it is critical to clean all cultures of these latent-appearing bacteria. To accomplish this, plantlets from in vitro were transferred to soil, watered with Dimanin® (2 ml/l) weekly and then reintroduced into in vitro. Of the 191 accessions processed for bacterial elimination, 100% tested bacteria-free after treatment. It is suspected that these bacteria may be endosymbionts and some may be beneficial for the plants.